A TRLFS study on the complexation of novel BTP type ligands with Cm(III) - Beele, Björn B.; Rüdiger, Elias; Schwörer, Felicitas; Müllich, Udo; Geist, Andreas; Panak, Petra (Dalton transactions, 2013)
Two BTP-type N-donor ligands with different numbers of aromatic nitrogen atoms (2,6-bis(4-ethyl-pyridazin-1-yl)pyridine, Et-BDP and 2,6-bis(4-npropyl-2,3,5,6-tetrazine-1-yl)pyridine, nPr-Tetrazine) have been synthesized and characterized by NMR and MS techniques. The complexation with Cm(III) in 2-propanol-water (1 : 1, vol.) is studied for both ligands using time resolved laser-induced fluorescence spectroscopy (TRLFS) and the complexation properties are compared to nPr-BTP. With increasing the ligand concentration three different species, the 1 : 1-, 1 : 2- and 1 : 3-complex, were found. Log β3 values of 7.6 for the formation of Cm(Et-BDP)3 and 9.2 for the formation of Cm(nPr-Tetrazine)3 are determined. The complexation with nPr-Tetrazine shows slow kinetics. Thermodynamic data of the complexation reactions are determined in a temperature range of 25 °C-60 °C. The complexation with Et-BDP is exothermic (ΔH = −16.3 ± 1.2 kJ mol−1) and exergonic (ΔG = −43.8 ± 2.6 kJ mol−1) whereas the complexation with nPr-Tetrazine is endothermic (ΔH = 43.9 ± 3.1 kJ mol−1) and exergonic (ΔG = −51.7 ± 2.2 kJ mol−1). In the case of the latter the complexation is driven by a highly positive reaction entropy change (ΔS = 320.6 ± 15.4 J mol−1 K−1). In comparison to nPr-BTP, less negative ΔG values were found for the complexation of Cm(III) with both ligands.
Gesehen am 30.11.2020